ПРОФИЛАКТИКА В СИСТЕМЕ ОКАЗАНИЯ МЕДИЦИНСКОЙ ПОМОЩИ. ЧТО СДЕЛАНО И ЧТО ПРЕДСТОИТ СДЕЛАТЬ? - С. А. Бойцов; Р. М. Линчак (Архивъ внутренней медицины)
The article analyzes causes of dramatic changes in structure of mortality in the world over past 100 years, sums up the experience of major regional projects and national programs carried out in different countries in Europe and North America and preventive measures with proven effectiveness in reducing mortality from non-communicable diseases. We give a list of activities carried out by the executive and legislative branches in Russian Federation, by specialists in medical prophylaxis in last 1,5–2 years, aimed at the prevention of major non-communicable diseases and health promotion. Place of medical prophylaxis in the healthcare system is detailed.